INSTASTORY PERILAKU KONSUMEN DI ERA NEW NORMAL - I Made Hariyoga; I Gusti Ngurah Putra Suryanata (Universitas Islam Bandung, 2021)
ABSTRACTThe aims of this study to determine consumer behavior and the stages of purchasing decisions due to Instastory marketing carried out by Griya Bakery & Griya Florist in the new normal era. The research method used is a qualitative method. Researchers conducted interviews with selected informants using the